Formation and study of collections of selected alternative crops - Anna MICHALOVÁ (Acta Agriculturae Slovenica)
The restoration of smaller farms, are in the Czech Republic formative conditions for the increase of acreage of several field crops which were in past years replaced by crops more suitable for the large-scale crop production. The problems of genetic resources of alternative crops have been studied at the Institute of Crop Production in Prague - Ruzyni since 1993. Non-traditional cereals (hulled wheats - spelt wheat,  einkorn wheat, emmer wheat; naked oat and barley, millet and the minor millets) and the "pseudocereals" (buckwheat, amaranth and quinoa) are collected and studied. Their high nutritional and dietetic values answer the requirements of the food industry and of the consumers.